Instrumented insole for mobile and long distance motion pattern measurement - David, V.; Jagos, H.; Litzenberger, S.; Reichel, M. (Procedia Engineering, 2012)
vitaliSHOE is a multimodal sensor system for insole motion measurement, originally developed for the assessment of gait parameters in ambient assisted living and rehabilitation by the Austrian research institute CEIT Raltec. It is diffcult to measure gait parameters in-situ, over longer periods of time and without affecting the user (e.g. in long-distance running). vitaliSHOE is a mobile and low-effort motion analysis system which measures pressure, acceleration forces in all three spatial directions and the angle between subsurface and insole of the users foot. All data are recorded with a sampling frequency of 50 Hz and a resolution of 10 bit and stored on a micro SD memory card. Evaluation of the pressure measurement system and the acceleration and angular data was carried out with medilogic (T&T, GER) and Vicon Peak Motus (USA), respectively. The majority of the results show very strong correlation (r > 0.9) between the data from vitaliSHOE and the corresponding reference systems, which represents a strong linear relationship.